Static analysis of boiler feed pump shaft in steam power plants: Enhancing durability and operational efficiency - Muhammad Athar Altarisi; Rifelino Rifelino; Delima Yanti Sari; Wanda Afnison (Researcher and Lecturer Society, 2024)
Centrifugal pumps are commonly used in industrial and domestic sectors to transport fluids by increasing their flow rate to a specific pressure. One type of centrifugal pump, the Boiler Feed Pump (BFP), plays a crucial role in steam power plants. Designed for continuous operation, BFP shafts are prone to wear and failure due to extreme operational conditions. This study employs computer-aided simulation using SolidWorks software to analyze von Mises stress, displacement, strain, and safety factors of BFP shafts with three material variations: AISI 4140, AISI 316, and AISI 304. The results indicate that AISI 4140 material exhibits the highest safety factor of 2.7 and the lowest displacement of 0.453 mm. Fatigue simulation also shows that AISI 4140 has the lowest damage percentage and the highest fatigue life. These findings suggest that AISI 4140 is the optimal material choice to enhance the durability and efficiency of shafts in applications requiring high reliability, such as BFPs in steam power plants.